Histological Structure of the Sclera in Three Species of Birds which Differ in Nutrition Nature - Taha, Ameer M.; Hamid, Hamid H. (International Journal of Scientific Research in Biological Sciences, 2020)
The present study dealt with the histological structure of the sclera in three species of birds that differ in their feeding, environmental, and classification. The birds were the sparrowhawk Accipiter nisus (carnivorous), the starling Sturnus vulgaris (Omnivorous), and zebra finch Taeniopygia guttata (granivorous). By using light microscopes, as well as the histological sections, had been stained with five different stains. The results of the sclera showed that it composed of collagenous fibers and hyaline cartilage with internal and external membranes the inner membrane appeared that they lined with pigment cells that differ in their density between the three species. The sclera appeared developed in the three species, but it more developed in the sparrowhawk. The most important results that appeared in this tunica, that the cartilage in both sparrowhawk and starling were separated in some parts of the eyeball by collagenous fibers and appeared the cartilage in sparrowhawk separated in some parts of the eyeball by blood vessels, as well as the cartilage contained pores which interspersed by blood vessels. While in the zebra finch, the cartilage was appeared in some regions separated by the blood canal. The cartilage ossifies in its connection area with the cornea in the sparrowhawk to form sclera bones, which not observed in the other two species. The cartilage also ossifies near the optic nerve to form optic nerve bone in both sparrowhawk and starling these not found in the zebra finch.